A blend of thyme and rosemary powders with poultry by-product meal can be used as a natural antioxidant in broilers - Alireza Hesabi Nameghi; Ommolbanin Edalatian; Reza Bakhshalinejad (Acta Scientiarum: Animal Sciences, 2022)
A total of 500, 14-d old male Ross 308 broilers were allocated into five treatments (4 replicates each) including: a negative (NC) and positive control diet (PC) which supplemented without and with 7% poultry by-product meal (PBPM), respectively and three levels of additive supplementation of thyme and rosemary powders in the basal diets: 0.750% rosemary powder (PCR); 0.375% thyme powder + 0.375% rosemary powder (PCRT), and 0.750% thyme powder (PCT) rosemary powder. The PCRT diet improved (p <0.05) average daily gain and feed conversion ratio by 5.62 and 10.37% compared to PC, respectively. The serum concentration of lipids (triglycerides, cholesterol, high-density lipoprotein, and low-density lipoprotein) was decreased while the ileal villus height and ratio of villus height to crypt depth as well as ileal microbiota population were improved (p <0.05) in response to inclusion PCRT diet compared to PC diet. The blood serum concentration of malondialdehyde was statistically decreased (p <0.05) by supplementation of PCRT in broiler diets. Our results suggested that supplementation of a blend of thyme and rosemary powders at the level of 0.375% of each into broiler diet during d 14-42 has merit to be used as a natural antioxidant in diets formulated by PBPM.